The Leap of the Tiger : How Malaysia Can Escape the Middle-Income Trap - Cherif, Reda (IMF Working Papers; Working Paper ;, 2015)
Only a few European economies and Korea and Taiwan Province of China reached high-income status during 1970-2010. Malaysia's real income per capita increased to 26 percent of the U.S. level in 2010 from 20 percent in 1970. Despite relatively strong growth and a substantial improvement in export sophistication, Malaysia's total factor productivity lagged behind that of Korea and Taiwan Province of China. We argue that what characterizes their experience in contrast to Malaysia's is the creation of technologies by domestic firms and a push to leapfrog to the technological frontier at an early stage of development.